Implementasi Program Magang Kampus Merdeka Di Stako Kopi UMS Untuk Memberikan Pengalaman Mahasiswa Dalam Berwirausaha - Abdulloh Faqih; Sitti Retno Faridatussalam (Universitas Muhammadiyah Surakarta, 2025)
The role of the Independent Entrepreneurial Internship opens up opportunities for students to prepare themselves for entrepreneurship. The unemployment problem in Indonesia is a serious problem for the government, therefore the purpose of this program is to provide a forum in the form of material and motivation for students who have an interest and talent in entrepreneurship so that it is hoped that it can improve economic conditions starting from a small scale. The method used is learning by doing so that problems that make it difficult for students to get the best solution. Data collection techniques using, (1) Direct experience of the author, (2) Direct field observation, (3) Documentation, (4) Interview through the manager of Stako Kopi UMS. Data analysis techniques using descriptive qualitative. This activity prepares young people who have an entrepreneurial spirit and applies the knowledge and skills gained in order to become entrepreneurs who can create jobs and have skills in managing a business. Keywords: Internship, Unemployment, Independent Entrepreneurship